The Great Mother archetype influence in bullying through Carrie (1974) by Stephen King - Marta G. Moreno (Feminismo/s, 2015)
The archetypes from the collective unconscious reveal some complexes that lie beneath the psyche and which are projected by it. Adolescence is a crucial moment when an inappropriate family environmental against its social development, it can suppose terrible consequences in the psychological development of the adolescent. Literature, as a reflection of our life experiences, is again a relevant analysis tool to explain, how matriarchy, can complicate a normal stage of development in adolescence. Through analytical psychology, the symbology of the archetypes will relate the Great Mother archetype and the influence in the bullying victim. Carrie (1974) will help us to explain these questions and how these experiences are assimilated by the psyche.